VD_FINDINFO HC / 2014 / 52 vom 17. Dezember 2013 - VD Tribunal cantonal (2013)
RETRAITVOIE DE DROIT, FRAIS JUDICIAIRES, DÉPENS | 106 al. 1 CPC (CH), 107 al. 1 let. b CPC (CH), 107 al. 1 let. f CPC (CH)